Purification and Characterization of Melanogenic Enzyme Tyrosinase from Button Mushroom. (14th August 2014) - Zaidi, Kamal Uddin; Ali, Ayesha S.; Ali, Sharique A.
Abstract : Melanogenesis is a biosynthetic pathway for the formation of the pigment melanin in human skin. A key enzyme, tyrosinase, catalyzes the first and only rate-limiting steps in melanogenesis. Since the discovery of its melanogenic properties, tyrosinase has been in prime focus and microbial sources of the enzyme are sought. Agaricus bisporus widely known as the common edible mushroom, it's taking place in high amounts of proteins, enzyme, carbohydrates, fibers, and low fat contents are frequently cited in the literature in relation to their nutritional value. In the present study tyrosinase from Agaricus bisporus was purified by ammonium sulphate precipitation, dialysis followed by gel filtration chromatography on Sephadex G-100, and ion exchange chromatography on DEAE-Cellulose; the enzyme was purified, 16.36-fold to give 26.6% yield on total activity in the crude extract and final specific activity of 52.19 U/mg. The SDS-PAGE electrophoresis showed a migrating protein band molecular weight of 95 kDa. The purified tyrosinase was optimized and the results revealed that the optimum values are pH 7.0 and temperature 35°C. The highest activity was reported towards its natural substrate, L-DOPA, with an apparent Km value of 0.933 mM. This indicated that tyrosinase purified from Agaricus bisporus is a potential source for medical applications.